STRATEGIC MANAGEMENT OF FOOTBALL CLUB DURING THE COVID-19 PANDEMIC - I. V. Solntsev (Стратегические решения и риск-менеджмент, 2021)
This research is aimed  to analyze the impact of the coronavirus pandemic on professional football clubs, identify the problems they face and propose strategic anti-crisis measures. The work is based on the analysis of the mapping study on measuring the economic impact of COVID-19 on the sport sector in the EU, provided by European Commission; analytical reports from Deloitte and KPMG containing empirical data on European football, academic research by foreign scientists examining the impact of the pandemic on the football industry. The study resulted in the author's strategic measures to improve the efficiency of football clubs in the face of restrictions caused by the spread of coronavirus, and a system of performance indicators (KPI), concerning the business developments during a pandemic. These results can be used in the strategic management of football clubs, as well as in the development strategies of federations, leagues and individual clubs, and can lead to an increase in the overall efficiency of their activities and the achievement of economic and social results. For the first time, the work carried out a comprehensive study of the consequences of the pandemic for the development of the football industry and offered the author’s view of solving current problems and finding new ways to develop the football business.